2013
DOI: 10.1155/2013/628094
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glucocorticoid Receptors in Dexamethasone-Induced Apoptosis of Neuroprogenitor Cells in the Hippocampus of Rat Pups

Abstract: Background. Dexamethasone (Dex) has been used to reduce inflammation in preterm infants with assistive ventilation and to prevent chronic lung diseases. However, Dex treatment results in adverse effects on the brain. Since the hippocampus contains a high density of glucocorticoid receptors (GCRs), we hypothesized that Dex affects neurogenesis in the hippocampus through inflammatory mediators. Methods. Albino Wistar rat pups first received a single dose of Dex (0.5 mg/kg) on postnatal day 1 (P1) and were sacrif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 46 publications
3
21
2
Order By: Relevance
“…We previously demonstrated that administering a single dose of Dex to P1 rat pups increased apoptosis in the dentate gyrus at P2 [12]. However in the current study, performance of behavioral tasks and morphology of granular cells at P56 were not impaired (Figs 1 and 3).…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…We previously demonstrated that administering a single dose of Dex to P1 rat pups increased apoptosis in the dentate gyrus at P2 [12]. However in the current study, performance of behavioral tasks and morphology of granular cells at P56 were not impaired (Figs 1 and 3).…”
Section: Discussioncontrasting
confidence: 68%
“…Dex administration reduces cerebral gray matter volume, indicating that it may potentially affect certain types of neuronal cells [810]. The affinity of Dex for the glucocorticoid receptors (GRs) is higher than mineralocorticoid receptors (MRs) [11,12]. In addition, the effects of glucocorticoids on learning and memory may be mediated through GRs [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the use of DEX has been associated with decreased apoptosis but with deleterious effects including a reduction in insulin-secreting cells [49], a decrease of neural progenitor cells in the hippocampus [50] and diminishing oligodendrocyte progenitor cells resulting in hypomyelination. More recently, a study showed that DEX increases apoptosis in osteoblast and osteocytes, leading to bone loss [51].…”
Section: Discussionmentioning
confidence: 99%
“…42 Methotrexate is associated with white matter changes in the brain, 43 acute seizures and paralysis, 44,45 and neurocognitive changes. 46 Corticosteroids can result in behavior changes 47 and decreased hippocampal functioning. 48 Vincristine can cause peripheral neuropathy.…”
Section: Org Frommentioning
confidence: 99%